Current and Future Perspectives on ADAMTS13 and Thrombotic Thrombocytopenic Purpura - Roose, Elien; Joly, Bérangère S. (Hämostaseologie, 2020)
Thrombotic thrombocytopenic purpura (TTP) is a rare, relapsing, and life-threatening disorder with an annual incidence of 10 cases per million people. TTP is a thrombotic microangiopathy characterized by severe thrombocytopenia, microangiopathic hemolytic anemia, and organ ischemia. The disease is caused by a severe deficiency of the enzyme ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 repeats, member 13), which can either be acquired, mainly by autoantibodies targeting ADAMTS13, or congenital due to mutations in the ADAMTS13 gene. Thanks to the establishment of national registries worldwide, fundamental and translational research, major advances have been made on the diagnosis, treatment, and fundamental understanding of TTP, since the description of the first TTP case almost 100 years ago. The introduction of therapeutic plasma exchange in the 1970s has significantly improved patient survival, but novel diagnostic assays, targeted treatments (rituximab, caplacizumab, recombinant ADAMTS13), and the unraveling of both ADAMTS13 function and TTP pathophysiology should help to further improve the patients' quality of life. However, differential diagnosis of TTP remains challenging and still a lot of questions remain unanswered to completely understand this rare and devastating disease.
Keywords: ADAMTS13; thrombotic thrombocytopenic purpura; treatment; diagnosis